Between a flock and a hard place [large type] - Andrews, Donna (Andrews, Donna. Meg Langslow mysteries, 2024)
"Meg's neighbors, the Smetkamps, have won a makeover from Marvelous Mansions, a flashy, yet dubious company focused on making historic homes more "modern." The company is already several days into its makeover, and tensions are running high between Mrs. Smetkamp, her neighbors, and the renovation crew. Meg arrives at the Smetkamps to find that a flock of feral turkeys has moved into their yard. Meg gathers a group of turkey wranglers, but when they arrive, they find the body of Mrs. Smetkamp in her backyard. Meg must figure out what happened . . . and what to do with these turkeys!"--